Innovative approach for efficient management of Ein Sultan Spring in Jericho - Musa Barghouthi A.H. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
Ein Sultan natural spring is a unique water source in Jericho for all uses. Only 48 percent of the springs' water is allocated to agriculture, much below its formal quote, but still subject to mounting pressures from non-agricultural competing sectors such as domestic, industrial and ecotourism. The time-share water right adds to the uncertainty of farmers' water security and induces inefficiency in allocating this valuable resource. The study is based on secondary data covering hydrology indicators of the spring system and primary data via interviewing farmers and agricultural extension agents. Despite the limited research inputs, the study gave a hint about the situation and enabled thoughtful discussion and extraction of useful suggestions. It showed possible causes of water use inefficiency, among which is the water supply driven irrigation (linked to water rights) rather than decisions based on crop water requirements, and lack of informed decisions at farm and policy making levels. The study emphasizes the need for institutional reform particularly reinforcing Ein Sultan Irrigation Water Cooperative as a water user association, and the need for information-based integrated irrigation water management strategy that tackle the spring as a unique socio-economic system, maintain water-rights and introduce water pricing policy which recognize water as valuable economic good. The study stresses the importance of active participation of farmers in designing and implementing such policies and measures.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)